Assessment of Decision Making Skills among Adolescents from Rural and Urban Contexts in Kenya: A Comparative Study of Learners in Public Secondary Schools in Nyeri and Nairobi Counties - Githui , Perminus; Njoka , Johannes N.; Mwenje , Margaret (African Journal of Education,Science and Technology (AJEST), 2018)
Human beings are confronted by situations that require them to make decisions every day in their lives. The natural processes of adjustment to situations in life that human beings are part of demands acts of decision making. Decision making is hence a natural consequence of existence by human beings. The purpose of this study was to assess the decision making skills among adolescents from rural contexts and those from urban environments. The study was guided by the following objectives which was to; assess the status of decision making skills among adolescents from rural and urban contexts in Kenya, evaluate the variables that influence adolescents during decision making processes from rural and urban environments in Kenya and analyze the challenges that face adolescents while making decisions from rural and urban contexts in Kenya. Descriptive research design was used in this study. Social cognitive theory developed by Bandura guided the study. The target population comprised of adolescents selected from schools from Nyeri and Nairobi Counties. A sample of schools from the two counties was selected using Kothari’s sampling formula which gave 30 (10%) schools from both counties. The sampled schools were as follows; 2 boys’ schools from each county, 3 and 2 girls’, 4 and 17 co-educational schools from Nyeri and Nairobi Counties respectively. Data was collected using a questionnaire administered to the sampled adolescents. The study used a sampling formula by Kathuri and Pals to determine the sample size which yielded 391 respondents. Analyzed data revealed that adolescents from urban areas had relatively better decision making skills compared to their counterparts from rural environments. The first hypothesis stated that there was no statistically significant difference in decision making abilities among adolescents from rural and urban contexts. To test this hypothesis, t-test was calculated which gave a level of significance .000 which was less than the p-value (.05). Therefore the null hypothesis was rejected. It was concluded that the decision making skills among adolescents from rural and urban contexts was dissimilar. The second research hypothesis sought to establish whether there was any statistically significant difference in decision making skills between gender from rural and urban contexts. The results of data analysis presented revealed that the level of significance .163 was more than the p-value (.05). Therefore the null hypothesis was accepted. It was concluded that there was no statistically significant difference in decision making skills among male and female adolescents. The study recommended that there is need to strengthen the process of nurturing decision making skills among adolescents in secondary schools in Kenya.